An interesting new record of the almost unknown brachypterous phaneropterine katydid Xenicola dohrni (Orthoptera: Tettigoniidae) from Argentina, and its high-ultrasound male-female communication - Braun, Holger (Zootaxa, 2021)
The southernmost record of the neotropical genus Xenicola is documented. An apparently tiny population of X. dohrni, a species described long ago from southern Brazil without other published records, lives at the shore of the Río de la Plata, 1000 km further south. Perhaps it has been established there by means of floating vegetation. The acoustic communication of this species is also very interesting: The male produces with its minuscule tegmina brief signals with a carrier frequency range between 80 and 100 kHz. The female responds, and the male modifies its song when engaged in a duet. It modifies it further, when the female responds from very close. The paper includes a review of the records of Xenicola species on biodiversity observation platforms.